Du manifeste Mon país escorjat, fin 1978, à la grève pour « Ladrecht », de mai 1980 à juin 1981 : un moment de rapprochement entre PCF et occitanistes. - Catherine Gossez (Lengas)
Starting from l’analysis of occitanist contribution to a social struggle led by the only Confédération Générale du Travail from may 1980 to june 1981, the strike for « Ladrecht » in Alès, this article try to understand how, from 1976, the French Communist Party and a part of occitanist militants with Robert Lafont especially, decided to work together.